On Fixed Point Theorem in Fuzzy Normed Space - Mohammed, Rana A; Ahmed, Buthainah A. A; S, Fadhel F (Al-Nahrain Journal of Science, 2018)
The formal balls in fuzzy normed space X (characterized by closed balls in X) are ordered by reverse inclusion depending on the concept of level sets. The set of formal balls in a fuzzy normed space is called a fuzzy domain normed space denoted by BX. This set is directed complete partially ordered set (dcpo), its maximal elements are the suprema. A contraction mapping principle is defined on BX. Banach fixed point theorem is studied and proved on BX.